29. Impact of Enhanced Influenza Vaccines on Direct Healthcare Costs for the U.S. Elderly: A Comprehensive Real-World Evaluation of Adjuvanted Trivalent Influenza Vaccine Compared to Trivalent High-Dose Influenza Vaccine for the 2018–19 Influenza Season. (31st December 2020) - Postma, Maarten; Pelton, Stephen I; Divino, Victoria; Mould-Quevedo, Joaquin F; Shah, Drishti; DeKoven, Mitchell; Krishnarajah, Girishanthy
Abstract: Background: Influenza generates a substantial economic burden (3.2B in the U.S. annually) due to direct medical costs such as physician office visits or hospitalizations, especially among the elderly. Recent published literature for the 2018–19 influenza season has demonstrated similar clinical effectiveness between adjuvanted trivalent influenza vaccine (aTIV) and trivalent high dose influenza vaccine (TIV-HD). This research aimed to assess the annualized mean all-cause and influenza-related healthcare costs among subjects 65+ years vaccinated with aTIV or TIV-HD during the 2018–19 influenza season. Methods: A retrospective cohort analysis was conducted using professional fee, prescription claims and hospital charge master data in the U.S. Baseline characteristics included age, gender, payer type, region, Charlson Comorbidity Index, comorbidities, indicators of frail health status, and pre-index hospitalization rates. Treatment selection bias was adjusted through 1:1 propensity score matching (PSM). Economic outcomes included annualized mean all-cause costs and influenza-related costs, which comprised influenza-related hospitalizations, emergency room (ER) visits, and physician office visits costs. Mean costs were compared using paired t-test. Adjusted analyses were conducted using generalized estimating equation (GEE) models, with two-part models for influenza-related costs. With the GEEs, adjustment for outliers (99th percentile) were addressed and predicted healthcare costs were obtained through bootstrapping (500 replications). Results: During the 2018–19 influenza season, the PSM sample comprised 561, 243 recipients of aTIV and 561, 243 recipients of TIV-HD. Following GEE adjustment, predicted mean annualized all-cause and influenza-related costs per patient were statistically similar between aTIV and TIV-HD (US9, 676 vs. US9, 625 and US23.75 vs. US21.79, respectively). Both aTIV and TIV-HD were comparable in terms of predicted mean annualized costs for influenza-related hospitalizations (US20.28 vs. US18.13) and influenza-related office visits (US1.29 vs. US1.34). Conclusion: In adjusted analyses, total all-cause and influenza-related healthcare costs were comparable among elderly subjects vaccinated with either aTIV or TIV-HD. Disclosures: Maarten Postma, Dr., IQVIA (Consultant) Stephen I. Pelton, MD, Merck vaccine (Consultant, Grant/Research Support)Pfizer (Consultant, Grant/Research Support)Sanofi Pasteur (Consultant, Other Financial or Material Support, DSMB)Seqirus Vaccine Ltd. (Consultant) Victoria Divino, PhD, Seiqrus Vaccines Ltd. (Consultant) Joaquin F. Mould-Quevedo, PhD, Seqirus Vaccines Ltd. (Employee, Shareholder) Drishti Shah, PhD, Seqirus Vaccines Ltd. (Consultant) Mitchell DeKoven, PhD, Seqirus Vaccines Ltd. (Consultant) Girishanthy Krishnarajah, PhD, Seqirus Vaccines Ltd. (Employee, Shareholder)